2021
DOI: 10.1038/s41467-021-24334-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 22 susceptibility loci associated with testicular germ cell tumors

Abstract: Testicular germ cell tumors (TGCT) are the most common tumor in young white men and have a high heritability. In this study, the international Testicular Cancer Consortium assemble 10,156 and 179,683 men with and without TGCT, respectively, for a genome-wide association study. This meta-analysis identifies 22 TGCT susceptibility loci, bringing the total to 78, which account for 44% of disease heritability. Men with a polygenic risk score (PRS) in the 95th percentile have a 6.8-fold increased risk of TGCT compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 91 publications
(98 reference statements)
0
46
0
Order By: Relevance
“…Genome-wide association studies (GWAS) have so far identified 78 susceptibility loci for TGCT ( 82 ). Although TGCT development is unique in several aspects, we know from GWAS that there are risk genes for TGCT that are involved in pathways commonly associated with other cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have so far identified 78 susceptibility loci for TGCT ( 82 ). Although TGCT development is unique in several aspects, we know from GWAS that there are risk genes for TGCT that are involved in pathways commonly associated with other cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, mRNA translation has been implicated in TGCT susceptibility for the first time; with several genes mapping to variants of significance identified by this recent GWAS, which encode proteins interacting in mRNA translation, including RPL4 , GSTP1 and TRAP-gamma [8 ▪▪ ].…”
Section: Germline Risk Of Germ Cell Tumoursmentioning
confidence: 94%
“…The SNPs identified in these GWAS map to several loci containing genes encoding proteins that are implicated in several biological pathways in TGCT susceptibility: male germ cell development, sex determination and maturation, regulation of the mitotic cell, and mRNA translation [8 ▪▪ ]. Knowledge about the functional importance of these loci has been predominantly acquired through studies on mouse models.…”
Section: Germline Risk Of Germ Cell Tumoursmentioning
confidence: 99%
See 1 more Smart Citation
“…According to genomic datasets, over three-quarters of the inherited genetic risk may be transmitted through common variation [ 6 ]. The inherited TGCT risk is largely polygenic [ 7 ], and genome-wide association studies have revealed 78 susceptibility loci for TGCT [ 8 ]. Functional studies show that a large part of the risk genes is related to male germ cell development, sex determination, and genomic integrity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%